2016
DOI: 10.3409/fb64_4.275
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Eisenia andrei (Oligochaeta; Lumbricidea) to Cadmium Polluted Soil Inhibits Earthworm Maturation and Reproduction but not Restoration of Experimentally Depleted Coelomocytes or Regeneration of Amputated Segments

Abstract: Exposure of Eisenia andrei (Oligochaeta; Lumbricidea) to cadmium polluted soil inhibits earthworm maturation and reproduction but not restoration of experimentally depleted coelomocytes or regeneration of amputated segments. Folia Biologica (Kraków) 64: 275-284. Lumbricid earthworms are often exposed to polluted soil. They are also commonly subjected to various stimuli and attacks by predators that induce extrusion of coelomocyte-containing coelomic fluid and/or the loss of body segments followed by the renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…If there is a lack of substances (e.g., enzymes) autophagy does not participate in cell survival, so processes of cell death as degeneration are activated intensively (Tettamanti et al 2008;Franzetti et al 2012;Park et al 2013;Karpeta-Kaczmarek et al 2016;Romanelli et al 2016). Ultrastructural and structural changes caused by cadmium have been detected in different organs in invertebrates, e.g., muscles, gonads, suprapharyngeal and subpharyngeal ganglions, and digestive system (Dallai 1966;Lauverjat et al 1989;Vega et al 1989;Siekierska & Urbańska-Jasik 2002;Siekierska 2003;Hödl et al 2010;Takacs et al 2016;Yuan et al 2016;Bednarska et al 2016Bednarska et al , 2019. A similar phenomenon has been observed in 12-and 45-day treated animals of L. forficatus because quantitative analysis revealed that regardless of the time of exposure to Cd, the decrease in cell viability was about 13%.…”
Section: Groupsmentioning
confidence: 99%
“…If there is a lack of substances (e.g., enzymes) autophagy does not participate in cell survival, so processes of cell death as degeneration are activated intensively (Tettamanti et al 2008;Franzetti et al 2012;Park et al 2013;Karpeta-Kaczmarek et al 2016;Romanelli et al 2016). Ultrastructural and structural changes caused by cadmium have been detected in different organs in invertebrates, e.g., muscles, gonads, suprapharyngeal and subpharyngeal ganglions, and digestive system (Dallai 1966;Lauverjat et al 1989;Vega et al 1989;Siekierska & Urbańska-Jasik 2002;Siekierska 2003;Hödl et al 2010;Takacs et al 2016;Yuan et al 2016;Bednarska et al 2016Bednarska et al , 2019. A similar phenomenon has been observed in 12-and 45-day treated animals of L. forficatus because quantitative analysis revealed that regardless of the time of exposure to Cd, the decrease in cell viability was about 13%.…”
Section: Groupsmentioning
confidence: 99%
“…Cadmium is a metal which, due to its high concentrations in air, water, and soil, rapid transport in the soil-plant-animal trophic chain, and high toxicity, is considered to be one of the most dangerous to both aquatic and terrestrial organisms (Descamps et al 1996;Satarug et al 2003;Wang et al 2013;Stalmach et al 2015;Tarnawska et al 2019). It affects different levels of body organization: from organs through tissues and cells to organelles and all the compounds synthesized (Vega et al 1989;Siekierska & Urbańska-Jasik 2002;Siekierska 2003;Hödl et al 2010;Babczyńska et al 2011;Takacs et al 2016;Yuan et al 2016;Bednarska et al , 2019Augustyniak et al 2017). Mitochondria are one of the organelles considered to be intracellular targets of cadmium.…”
Section: Introductionmentioning
confidence: 99%
“…fetida are explicitly required by the international Guidelines [ 1 , 2 , 3 ] as test species in ecotoxicology (e.g. [ 4 7 ]), and are widely used as models for basic studies in vermicomposting (e.g. [ 8 , 9 ]), and biomedicine [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%